Program Membangun Desa Melalui Sosialiasi Stunting dan Program Gemari Mahasiswa Kukerta UNRI 2023 (Jurnal Abdimas STMIK Dharmapala, 2024)
Stunting is a condition where a child’s growth and physical development is chronically hampered due to a lack of adequate nutritional intake, especially in the first 1,000 days of life (from pregnancy to two years of age). The main factors that cause stunting are malnutrition, lack of nutritious food intake, recurrent infections, poor hygiene and inadequate health services.Developmental delays can have serious long-term impacts on a child’s physical, cognitive and social development. This can lead to reduced cognitive abilities, productivity, and quality of life in adulthood.Reducing stunting requires a holistic approach from government, society and the health and nutrition sector.Enjoying eating fish is a healthy eating habit, because fish is rich in protein, omega-3 fatty acids and other important nutrients. Omega-3 fatty acids in fish play an important role in children’s brain development and can help prevent stunting. Therefore, encouraging children to enjoy eating fish can be a positive step in overcoming the problem of stunting.The method used in this activity is stunting outreach and the hobby program at the posyandu in Koto Inuman village. Our main target for this stunting outreach and fun program is toddlers, children, pregnant women and the elderly, which is carried out at the Koto Inuman village posyandu to increase knowledge about the dangers of stunting. The aim of the socialization of stunting prevention and the enjoyment program carried out by Kukerta Unri students in Koto Inuman village 2023 is so that the people of Koto Inuman village are protected from the dangers of stunting. The results obtained from this socialization are that the people of Koto Inuman village can recognize the impact of the dangers of stunting and what factors can cause stunting, as well as increase fish consumption for the benefit of children, toddlers and pregnant women, in Koto Inuman village.